The influence of interdisciplinary literacy on learning effects among college students: the mediating effects of online physical education on learning behavior - Zhang, Qi; Chen, Shan Ping; Hang, Lanping (Frontiers in Education, 2023)
Introduction The development of high-quality physical education curriculums is required in the information age. Interdisciplinary literacy and student learning behavior are two significant factors that affect the quality of teaching and learning. This study explores the relationship between interdisciplinary literacy (IDL) and learning effects (LE) among Chinese college students during the COVID-19 pandemic, as well as the mediating effects of online physical education learning behaviors (OPELB). This research aims to provide a reference for the development of high-quality online physical education. Methods The study involved 691 college students from 10 general universities in Shaanxi Province as research subjects. Descriptive statistics, Pearson correlation analysis, multiple regression analysis and Bootstrap testing were used to evaluate the mediating effects. Results There was a significant positive relationship between the three variables of IDL, OPELB, and LE (p < 0.001). Multiple regression analysis found that IDL significantly and positively predicted LE and OPELB (p < 0.001), and OPELB predicted LE (p < 0.001). IDL among college students had a total effect of 0.816 on LE, with OPELB accounting for 22.67% of the mediated effect. Discussion This study demonstrates that OPELB has a partial mediating effect on IL and LE, and stable IDL and OPELB improve LE. Therefore, teachers should pay attention to improving students’ IDL while encouraging them to develop better OPELB to achieve satisfactory learning outcomes.